Perceived Usefulness, Perceived Ease of Use, Facilitating Condition, Social Influence, and Personal Innovativeness of Accounting Students Cloud Computing Adoption - Kholilah Kholilah; Hisky Ryan Kawulur; Imam Subekti (Organum: Jurnal Saintifik Manajemen dan Akuntansi, 2022)
This study aims to test the influence of perceived usefulness, perceived ease of use, facilitating condition, social influence, and personal innovativeness in cloud computing adoption. This research is important because of the high demands of understanding student technology which can be started by adopting cloud computing in learning. Students can use cloud computing to share information, assignments, and work that can be accessed with various devices. This research was conducted on students at two state universities in Indonesia. The study used SEM in the analysis process. This research was conducted on students at two state universities in Indonesia. The results of questionnaire to 126 students indicate that the intention to use the cloud is determined by the perceived ease of use and facilitating condition. Three other variables used, perceived usefulness, social influence, and personal innovativeness were not shown to have an effect on cloud computing adoption intentions. The implication of this research is continuous research related to the use of information systems in learning.